Uji daya mesin diesel dengan hot EGR menggunakan bahan bakar campuran biosolar, metanol kadar rendah, dan jatropha - Yafid Effendi; Syaiful Syaiful (Universitas Muhammadiyah Metro, 2019)
Motorized vehicles that are very suitable for transportation and heavy equipment vehicles are diesel engines, because their high combustion efficiency, reliability, fuel flexibility, and low fuel consumption make diesel widely used in several countries. The purpose of this study was to determine the effect of using a mixture of biosolar fuels, low levels of methanol and jatropha on power in a diesel engine using the hot Exhaust Gas Recirculation (EGR) system. This study uses an experimental method, using a 4JB1 diesel engine, the percentage of biodiesel fuel mixture, low levels of methanol and jatropha, Low Purity Methanol has a moisture content of 24.88%. The ratio of biosolar mixture, methanol and jatropha used are D85LPM5J10, D80LPM10J10, D75LPM15J10, D75LPM5J20, D70LPM10J20, D65LPM15J20, D65LPM5J30, D60LPM10J30 and D55LPM15J30. EGR openings vary from 0%, 25%, 50%, 75% and 100%. The test is carried out at a constant speed of 2000 rpm and is given a load of 25%, 50%, 75% and 100%. This study uses a dynamite brand Land & Sea dynamite. The results of this study are the use of EGR resulted in increasing the value of brake power. The effect of the fuel mixture causes the value of brake power tends to fall compared to D100. When using D85LPM5J10, D80LPM10J10, D70LPM10J20 and D55LPM15J30 at low loads (25%) there is an increase in power by 12.03%, 7.50%, 5.01%, and 5.97%. Keywords: Power, Engine, Diesel, LPM, Jatropha, EGR.